2006
DOI: 10.1002/mnfr.200600086
|View full text |Cite
|
Sign up to set email alerts
|

Heterocyclic amines: Chemistry and health

Abstract: Heterocyclic amines (HAs) occur at the ppb range in foods. Most of them demonstrate potent mutagenicity in bacteria mutagenicity test, and some of them have been classified by the International Agency for Research on Cancer as probable/possible human carcinogens. Their capability of formation even during ordinary cooking practices implies frequent exposure by the general public. Over the past 30 years, numerous studies have been stimulated aiming to alleviate human health risk associated with HAs. These studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
63
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(65 citation statements)
references
References 229 publications
(403 reference statements)
0
63
0
1
Order By: Relevance
“…15,16,18 -21,24 -26 Nutrients that are thermally prepared for consumption are a rich source of protein-or fat-derived oxidation derivatives, including AGEs, and a host of toxic compounds in foods, some of which have been implicated in oncogenesis. [27][28][29][30][31][32] Laboratory rodent food is high in protein, low in fat, supplemented with micronutrients, and routinely heated to ensure safety. The temperatures currently used are sufficiently high to inadvertently cause standard mouse chow to be rich in oxidant AGEs, not unlike levels present in the usual Western diet.…”
mentioning
confidence: 99%
“…15,16,18 -21,24 -26 Nutrients that are thermally prepared for consumption are a rich source of protein-or fat-derived oxidation derivatives, including AGEs, and a host of toxic compounds in foods, some of which have been implicated in oncogenesis. [27][28][29][30][31][32] Laboratory rodent food is high in protein, low in fat, supplemented with micronutrients, and routinely heated to ensure safety. The temperatures currently used are sufficiently high to inadvertently cause standard mouse chow to be rich in oxidant AGEs, not unlike levels present in the usual Western diet.…”
mentioning
confidence: 99%
“…269 3). Separation of HCAs has traditionally been achieved under acidic LC conditions 270 [1,12], on the principle that mobile phase pH should be lower than the analyte pKa (<pH 271 5 for the HCAs) in order to fully protonate the HCA amine groups prior to positive mode 272 electrospray ionisation. However, baseline chromatographic separation of the DiMeIQx 273 isomers is sensitive to pH and is incomplete under the commonly used pH 4.7 or lower 274…”
Section: Lc-ms/ms Optimisation 261mentioning
confidence: 99%
“…Heterocyclic aromatic amines (HCA) are formed during combustion of tobacco and cooking of proteinrich foods, particularly meat and fish, which provide creatin(in)e and other precursors such as amino acids, sugars or other aldehydes (Cheng et al, 2006;Puangsombat et al, 2012;Aaslyng et al, 2013). 2-Amino-1-methyl-6-phenylimidazo(4,5-b)pyridine (PhIP), 2-amino-3,8-dimethylimidazo[4,5-f]quinoxaline (MeIQx) and 2-amino-3,4,8-trimethylimidazo[4,5-f]quinoxaline (4, are three of the most abundant HCAs in cooked meat and fish (Lynch et al, 1995;Zhang et al, 2013) although many others have been identified (Ni et al, 2008).…”
Section: Introductionmentioning
confidence: 99%